Isolement et Identification des bactéries lactiques à partir de blé fermenté type « HAMMOUM » - BEKADDOURI KHEIRA, LOUISA; BELAYACHI, ASMAA (My University, 2020)
Cereals are the basis of human nutrition. The grains of fermented wheat "hammoum" is a wheat that has spent a long time in an underground silo. », Rich in biologically active substances, which gives it great interest in terms of phytotherapy. The objective of this work is to bring out the particularities of this raw material by an in-depth characterization of its main metabolites, targeted according to their biological properties and shown to have a protective effect of certain lactic acid bacteria isolated from this fermented wheat 10 isolates have were selected and pre-identified by conventional phenotypic methods using the various usual tests (growth at different concentrations, heat resistance, etc.). Studies of the main morphological, biochemical and physiological characters of the lactic microflora of wheat firmness were performed following recommendations from similar studies. 10 isolates were Gram positive, catalase negative, citrate and nitrate negative (most cocci forms). These immobile lactic acid bacteria do not produce acetoin or hydrogen sulfide (H2S). These strains are also all capable of growing at 45 ° C.
Keywords: Lactic acid bacteria; hammoum; probiotic; isolation .